Clutches, broods, and brood care behaviour in Chestnut Teal - Norman, F I; McKinney, F (Wildfowl, 1987)
Details of clutch sizes and subsequent productivity are presented for Chestnut Teal Anas castanea using artificial nest boxes. Survival of ducklings marked in the nests and subsequently trapped is discussed in relation to contemporary counts of broods. The role of both parents in brood care was investigated. Clutch sizes were affected by the disappearance of marked eggs and by the presence of eggs from previous clutches and other females. There was little evidence to show between season variations in clutch sizes but separation into early, mid, or late season clutches did show some differences. Relatively few tagged ducklings were found dead in boxes but mortality, particularly in the period immediately after leaving the boxes, was high. In general, broods of all ages were smaller when no parent was in attendance, and broods attended by both parents were larger than those accompanied by a single parent of either sex. Male Chestnut Teal attendance declined with increasing brood age. Males were observed to take active roles in brood protection and defense. It is concluded that males are not accompanying broods primarily to maintain a pair-bond, but rather they are protecting the smaller ducklings especially prone to predation.